Genetic and clinical determinants of MACE and haemorrhage in antiplatelet therapy: insights from pharmacogenomic analysis - Wang, Yubo; Yuan, Shuangli; Li, Muyun; Feng, Wenling; Li, Jing; Chen, Wenwen; Berdi, Aliye; Kou, Yulian; Yuan, Yuan; Zhao, Jun (Frontiers in Cardiovascular Medicine, 2025)
BackgroundVariability in responses to clopidogrel and aspirin therapy for coronary artery disease has driven interest in pharmacogenomics. This study investigates the role of genetic variants in CYP2C19, ABCB1, and PON1 in predicting adverse cardiovascular events and guiding personalised antiplatelet therapy.MethodsA retrospective cohort study designed to compare the effectiveness and safety of the risk levels from CYP2C19 (*2, *3, *17), ABCB1 C3435T, and PON1 Q192R polymorphisms. The primary outcome was the incidence of haemorrhage and major adverse cardiovascular events (MACE). Kaplan Merir curves and Cox regression with IPTW adjustments were used for analysis.ResultsThe results of this study indicate that patients in Group A, who received treatment consistent with multigene testing (CYP2C19, ABCB1, and PON1), experienced significantly lower major adverse cardiovascular events (MACE) compared to Group B. Multigene testing proved to be more accurate in predicting clopidogrel effectiveness and reducing adverse events without an increased risk of haemorrhage (HR 0.671, 95% CI: 0.526–0.855, P = 0.001). Patients in Group A showed no significant difference in haemorrhage risk compared to Group B, with an HR of 0.831 (95% CI: 0.598–1.155, P = 0.271) after adjustment.ConclusionMultigene-guided antiplatelet therapy is more effective in reducing adverse cardiovascular events. Further prospective studies are needed to validate these findings, incorporating genetic, environmental, and lifestyle factors for a comprehensive personalised medicine approach.